Effect of machining parameters on cutting force during dry milling of 2205 DSS and 2507 SDSS materials. (2021) - George, Pradeep; Leo Dev Wins, K.; Ebenezer Jacob Dhas, D.S.; George, Pramod; Anuja Beatrice, B.
Highlights: In this study, the effect of machining parameters on cutting force was evaluated. Experiments were conducted by varying feed rate and spindle speed. Results exhibited a decrease in cutting force with increase in spindle speed. Cutting force increased with feed rate for both 2205 DSS and 2507 SDSS grades. Results showed that feed rate and spindle speed have greater effect on cutting force. Abstract: Duplex Stainless Steels (DSS) contain high chromium content and hence DSS are considered as difficult to machine material due to their exceptional strength and other physical properties. DSS are extensively used in food industries, petrochemical, Transport, paper making industries, pollution control equipments, sea water processing. In this study, the effect of machining parameters on cutting force was evaluated during CNC dry milling of 2205 Duplex Stainless Steel (2205 DSS) and 2507 Super Duplex Stainless Steel (2507 SDSS). Experiments were conducted by varying feed rate and spindle speed. Results exhibited a decrease in cutting force with a rise in spindle speed until 4200 rpm and beyond that it increased with the increase in spindle speed for both materials. When feed rate was increased, cutting force values increased for both 2205 DSS and 2507 SDSS grades. Higher cutting force values were recorded while machining 2507 SDSS compared to 2205 DSS under same cutting conditions. This is mainly due to the presence of high percentage of chromium content in 2507 SDSS material. From the analysis, it was noticed that spindle speed and feed rate have greater effect on cutting force during CNC dry milling operation.